2010
DOI: 10.1016/j.phymed.2009.10.011
|View full text |Cite
|
Sign up to set email alerts
|

An aqueous extract of Ammi visnaga fruits and its constituents khellin and visnagin prevent cell damage caused by oxalate in renal epithelial cells

Abstract: Teas prepared from the fruits of Ammi visnaga L. (syn. “Khella”) have been traditionally used in Egypt as a remedy to treat kidney stones. It was the aim of our study to evaluate the effect of a Khella extract (KE) as well as the two major constituents khellin and visnagin on renal epithelial injury using LLC-PK1 and Madin-Darby-canine kidney (MDCK) cells. Both cell lines provide suitable model systems to study cellular processes that are possibly involved in the development of a renal stone. LLC-PK1 and MDCK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 29 publications
(39 reference statements)
2
59
0
4
Order By: Relevance
“…These compounds (Figure 1) are tetracosanoic acid (1), β-sitosterol (2), visnadine (3), khelllin (4), β-sitosterol glucoside (5), norkhellol (6), khellol (7), rhmnazin (8), cimifugin (9) and cis-khellactone-3'-β-glucopyranoside (10 mifugin (9) at concentration of 40 μg/mL showed cytotoxicity on B16 melenoma cells rather than melanin formation inhibition; β-sitosterol (2) and β-sitosterol glucoside (5) had no effect on melanin inhibition. Previously, khellin was reported to have some biological effects such as smooth muscle relaxant [20] and prevention of stone formation associated with hyperoxaluria [8], while in our study we concluded that khellin (4) is a promising compound which could be useful for treating hyperpigmentation, as a skin-whitening agent with less toxicity even than the standard drug arbutin. To the best of our knowledge, we obtained this compound from the waste of A. visinaga which caused a serious problem so we can get a great beneficial from these waste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds (Figure 1) are tetracosanoic acid (1), β-sitosterol (2), visnadine (3), khelllin (4), β-sitosterol glucoside (5), norkhellol (6), khellol (7), rhmnazin (8), cimifugin (9) and cis-khellactone-3'-β-glucopyranoside (10 mifugin (9) at concentration of 40 μg/mL showed cytotoxicity on B16 melenoma cells rather than melanin formation inhibition; β-sitosterol (2) and β-sitosterol glucoside (5) had no effect on melanin inhibition. Previously, khellin was reported to have some biological effects such as smooth muscle relaxant [20] and prevention of stone formation associated with hyperoxaluria [8], while in our study we concluded that khellin (4) is a promising compound which could be useful for treating hyperpigmentation, as a skin-whitening agent with less toxicity even than the standard drug arbutin. To the best of our knowledge, we obtained this compound from the waste of A. visinaga which caused a serious problem so we can get a great beneficial from these waste.…”
Section: Resultsmentioning
confidence: 99%
“…visinaga extracts have demonstrated to have a broad range of therapeutic effects such as antihyperglycemic [5], vasodilator effect [6], anti-inflammatory [7], and inhibition of oxalate nephrlithiasis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to find for an alternative means such as medicinal plants or phytotherapy [5]. Data from in vitro, in vivo studies and clinical trials reveal that phytotherapeutic agents could be useful as either an alternative or an adjunctive therapy in the management of urolithiasis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The seeds are tiny (about 2 mm long) and oval-shaped and have been used in traditional medicine to make herbal remedies to treat kidney stones [1]. Recent laboratory studies have shown that an aqueous extract of the seeds acts as a diuretic and inhibits the formation of calcium oxalate crystals in the kidneys and prevents cell damage caused by oxalate in renal epithelial cells [2]. Plants in the apiaceae family are good sources of biologically active compounds [3]- [5].…”
Section: Introductionmentioning
confidence: 99%